O‘Rta Osiyo Xalqlari Tarixida Ko‘Chmanchi Chorvador Qabilalarning Tutgan O‘Rni - o‘g‘li, Aliboyev Dilshod Davron; Akhmadkulovich, Abdumatov Alisher; o‘g‘li, Rayimjonov Ismoiljon Xoshimjon (Journal of Innovation in Education and Social Research, 2025)
This article analyzes the governance system of the nomadic peoples of Central Asia. It examines the political structure of nomadic societies, the rules of military democracy, popular assemblies, hereditary kingdoms, and their role in state governance. During the study, based on various historical sources, the factors that influenced the formation of the nomadic governance system, including the interaction with peasant and urban communities, are studied. The specific aspects of the political organizations and governance institutions of nomadic peoples are also highlighted.